Fungal bioassays for environmental monitoring - Soares, Douglas M. M.; Procópio, Dielle P.; Zamuner, Caio K.; Nóbrega, Bianca B.; Bettim, Monalisa R.; de Rezende, Gustavo; Lopes, Pedro M.; Pereira, Arthur B. D.; Bechara, Etelvino J. H.; Oliveira, Anderson G.; Freire, Renato S.; Stevani, Cassius V. (Frontiers in Bioengineering and Biotechnology, 2022)
Environmental pollutants are today a major concern and an intensely discussed topic on the global agenda for sustainable development. They include a wide range of organic compounds, such as pharmaceutical waste, pesticides, plastics, and volatile organic compounds that can be found in air, soil, water bodies, sewage, and industrial wastewater. In addition to impacting fauna, flora, and fungi, skin absorption, inhalation, and ingestion of some pollutants can also negatively affect human health. Fungi play a crucial role in the decomposition and cycle of natural and synthetic substances. They exhibit a variety of growth, metabolic, morphological, and reproductive strategies and can be found in association with animals, plants, algae, and cyanobacteria. There are fungal strains that occur naturally in soil, sediment, and water that have inherent abilities to survive with contaminants, making the organism important for bioassay applications. In this context, we reviewed the applications of fungal-based bioassays as a versatile tool for environmental monitoring.